Male Rape, Masculinities, and Sexualities Understanding, Policing, and Overcoming Male Sexual Victimisation - Javaid, Aliraza (Cham : Springer International Publishing, 2018)
This book critically explores the intersections between male rape, masculinities, and sexualities. It examines the ways in which male rape is policed, responded to, and addressed by state and voluntary agencies in Britain. The book uncovers how notions of gender, sexualities and masculinities shape these agencies' understanding of male rape and their views of men as victims of rape. Javaid pays particular attention to the police and deconstructs police subculture to consider whether it influences and shapes the ways in which police officers provide services for male rape victims. Grounded in qualitative interviews and data derived from the state and voluntary sector, this book will be invaluable reading for sociologists, criminologists, and social scientists who are keen to learn more about gender, policing, sexual violence and male sexual victimisation.
1. Gendering Rape: (Dis)connecting Men and Rape -- 2. Uncovering Male Sexual Victimisation -- 3. Researching Male Sexual Victimisation: "The Personal is Political" -- 4. The Sociology of Gender, Sexualities and Masculinities -- 5. The Criminal Justice System and Male Rape: Processing Male Rape Cases -- 6. Responding to Male Sexual Victimisation: (Un)supporting Male Rape Victims. .
Law and Criminology
text file PDF
Keywords: Critical criminology; Crime-Sociological aspects; Police; Corrections; Punishment; Sociology